2021
DOI: 10.1038/s41598-021-82297-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cord blood hematological parameters among normal, α-thalassemia, and β-thalassemia fetuses between 17 and 38 weeks of gestation

Abstract: The aim of this study was to retrospectively compare hematological parameters among normal, α-, and β-thalassemia fetuses between 17 and 38 weeks of gestation. Pregnant women at risk of having fetuses with thalassemia major and underwent cordocentesis for prenatal diagnosis were recruited. Fetal cord blood samples were collected from 249 fetuses for hematological and DNA analysis. Fetuses were divided into subgroups according to thalassemia DNA genotypes. The average and gestational age of subjects were 27.95 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 20 publications
1
10
1
Order By: Relevance
“… 18 Hematological parameters have been used for years to provide information about the health status of the fetus. 3 The cord blood hematological data provide data on the health status of the fetus in the related period of pregnancy. These indices could be changed according to the mutations identified in the fetus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 18 Hematological parameters have been used for years to provide information about the health status of the fetus. 3 The cord blood hematological data provide data on the health status of the fetus in the related period of pregnancy. These indices could be changed according to the mutations identified in the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha (α-) and beta (β-) thalassemias are the two major types that are caused by deficient synthesis of α- and β-globin chains . 3 , 4 , 5 Structural Hb variants are developed by single amino acid substitutions in the α- or β-globin chains. 6 One of the most common Hb variants is sickle cell anemia (SCA), and in the South part of Turkey, the prevalence of sickle-cell Hb (HbS) is 10% in the Çukurova region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that hematological parameters varied with gestational age. An increase in gestational age is associated with increased Hb and Hct and decreased MCV, MCH, and MCHC values [ 27 29 ]. In addition, a co-inheritance of the Hb E, which is a β-globin chain variant, in patient 2 may help in the improvement of the hematological phenotype of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…β-thalassemia is a blood disorder that reduces the production of hemoglobin. Although studies concerned have suggested that several cord blood serum markers have potential diagnostic value, they have not been worked in application [58]. The relatively mature enough technique is the GthapScreen HBB kit, which involves several STR markers.…”
Section: β-Thalassemiamentioning
confidence: 99%